Key Challenges and Suggestions to Enhance Effectiveness in Online EFL Instructions from Teacher’s and Stude’s Perspectives - Labadi Razika (My University, 2025)
Abstract This current study aims to investigate the key challenges encountered in online English as a foreign language ( EFL) instruction from both teachers and learners perspectives . It also seeks to propose practical suggestions to enhance the effectiveness of online EFL teaching and learning. To achieve these objectives, a mixed- method approach was employed. An online questionnaire was distributed to 83 second-year English students, while semi structured interviews were conducted with six EFL teachers from the English department at the University of Mohamed Cherif Messaadia, Souk Ahras. The findings reveal that both teachers and learners face several pedagogical, technical, and psychological challenges in the online learning environment. However, the study also highlights various strategies and recommendations provided by both parties to overcome these difficulties and improve the quality of online instruction. Based on the confirmed hypotheses, pedagogical implications are suggested, emphasizing the need for professional training, improved infrastructure, and interactive teaching methods to foster a more effective and engaging online EFL experience. ------------------- هذه الدراسة الى استكشاف التحديات الرئيسية التي تواجه تعليم اللغة الانجليزية كلغة اجنبية عبر الخط من منظور المعلمين والمتعلمين على حد سواء. كما تسعى الى تقديم اقتراحات عملية لتعزيز فعالية تدريس وتعلم اللغة االنجليزية الكترونيا. لتحقيق هذه الاهداف تم اعتماد منهجية مختلطة حيث وزع استبيان الكتروني على 83 طالبا من طالب السنة مهيكلة مع ستة اساتذة من قسم اللغة الانجليزية بجامعة محمد الشريف الثانية بقسم اللغة الانجليزية واجريت مقابلات شبه في سوق اهراس. كشفت النتائج ان المعلمين والمتعلمين يواجهون عدة تحديات تربوية وتقنية ونفسية في بيئة مساعدية ومع ذلك تسلط الدراسة الضوء ايضا على استراتيجيات وتوصيات متنوعة قدمها الطرفان لتجاوز التعلم عبر لانترنيت. هذه الصعوبات وتحسين جودة التدريس واستنادا الى الفرضيات المؤكدة تقترح الدراسة دلالات تربوية تؤكد على ما يعزز تجربة اكثر فعالية وجاذبية في ضرورة التدريب المهني وتحسين البنية التحتية واعتماد اساليب تدريس تفاعلية تعلم اللغة الانجليزية كلغة اجنبية عبر الانترنيت . --------------- Résumé La présente étude vise à identifier les principaux défis rencontrés dans l’enseignement de l’anglais comme langue étrangère (EFL) en ligne, du point de vue des enseignants et des apprenants. Elle cherche également à proposer des suggestions pratiques afin d’améliorer l’efficacité de l’enseignement et de l’apprentissage de l’EFL en ligne. Pour atteindre ces objectifs, une approche méthodologique mixte a été adoptée : un questionnaire en ligne a été distribué à 83 étudiants de deuxième année en anglais, tandis que des entretiens semi-structurés ont été menés avec six enseignants du département d’anglais de l’Université Mohamed Chérif Messaadia de Souk Ahras. Les résultats révèlent que les enseignants comme les apprenants font face à plusieurs défis d’ordre pédagogique, technique et psychologique dans l’environnement d’apprentissage en ligne. Cependant, l’étude met également en évidence diverses stratégies et recommandations proposées par les deux parties pour surmonter ces difficultés et améliorer l’efficacité pédagogique . Sur la base des hypothèses confirmées, des implications pédagogiques sont suggérées, mettant l’accent sur la nécessité d’une formation professionnelle, d’une infrastructure améliorée et de méthodes d’enseignement interactives, en vue de favoriser une expérience d’apprentissage de l’EFL en ligne plus efficace et engageante.
Keywords: Online EFL instruction; teacher perspectives; students’ perspectives; challenges; student engagement; instructional effectiveness; اللغة الانجليزية كلغة ثانية عبر الخط - منظور المعلمين والمتعلمين- فعالية تدريس وتعلم اللغة الانجليزية- الصعوبات; L’enseignement de l’Anglais langue étrangère en ligne; point de vue des enseignants et des apprenants; perspectives des étudiants; défis; l’efficacité pédagogique